2018
DOI: 10.3847/1538-4357/aac490
|View full text |Cite
|
Sign up to set email alerts
|

Revealing the Nature of Blazar Radio Cores through Multifrequency Polarization Observations with the Korean VLBI Network

Abstract: We study the linear polarization of the radio cores of eight blazars simultaneously at 22, 43, and 86 GHz with observations obtained by the Korean VLBI Network (KVN) in three epochs between late 2016 and early 2017 in the frame of the Plasma-physics of Active Galactic Nuclei (PAGaN) project. We investigate the Faraday rotation measure (RM) of the cores; the RM is expected to increase with observing frequency if core positions depend on frequency due to synchrotron self-absorption. We find a systematic increase… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
35
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 26 publications
(42 citation statements)
references
References 119 publications
6
35
1
Order By: Relevance
“…We interpret this shift as a sign of Faraday rotation, and plot the values of these maxima relative to the square of wavelength in the bottom panel of the same figure. The values of the rotation measure (RM) obtained in this way for the pairs of frequencies 10 5.6 -229 GHz, 229-86 GHz, and 86-43 GHz are, correspondingly, −35100 ± 3000, −7900 ± 1000, and −1900 ± 500 rad·m −2 . Neither the signs nor frequency dependence of the RM contradict earlier determinations (see, e.g., Kang et al 2015;Park et al 2018). Figure 17 shows the dependencies of the optical PD on Rband flux density for different stages of activity (1)-(4), as defined in $ 3.6.…”
Section: Relationship Between Multiwavelength Variability and Changesmentioning
confidence: 63%
“…We interpret this shift as a sign of Faraday rotation, and plot the values of these maxima relative to the square of wavelength in the bottom panel of the same figure. The values of the rotation measure (RM) obtained in this way for the pairs of frequencies 10 5.6 -229 GHz, 229-86 GHz, and 86-43 GHz are, correspondingly, −35100 ± 3000, −7900 ± 1000, and −1900 ± 500 rad·m −2 . Neither the signs nor frequency dependence of the RM contradict earlier determinations (see, e.g., Kang et al 2015;Park et al 2018). Figure 17 shows the dependencies of the optical PD on Rband flux density for different stages of activity (1)-(4), as defined in $ 3.6.…”
Section: Relationship Between Multiwavelength Variability and Changesmentioning
confidence: 63%
“…If the Faraday screen is placed in the immediate vicinity of the jet, e.g., like a sheath surrounding the jet as claimed for other distant AGNs (e.g., Zavala & Taylor 2004;Jorstad et al 2007;O'Sullivan & Gabuzda 2009;Hovatta et al 2012;Park et al 2018), then one expects significant RM gradients across the jet with a possible change of the sign of the RM; this is seen in numerical simulations (Broderick & McKinney 2010). This signature has indeed been frequently observed in the jets of many blazars (e.g., Asada et al 2002Asada et al , 2008Gabuzda et al 2004Gabuzda et al , 2018Hovatta et al 2012).…”
Section: A Jet Sheathmentioning
confidence: 99%
“…Note that significant progress in blazar polarimetry has also been obtained from radio facilities in mm/submm bands (86/129/230/300 GHz), thanks to the advent of ALMA as well as KVN/GMVA. In particular, recent mm/submm RM measurements of blazars consistently show a systematic increase of RM magnitude towards higher frequencies [162,183,184], reaching as high as 10 5−8 rad m −2 , which are at least ∼2-5 orders of magnitude higher than those typically measured at low frequencies. This strongly indicates the existence of dense Faraday screens and/or strong, highly-ordered B-fields towards the jet base, as expected by magnetic-driven jet models.…”
Section: Polarimetric Propertiesmentioning
confidence: 76%
“…A systematic KVN study for a sample of γ-ray blazars find that the core spectra in their samples systematically become steeper at 86-129 GHz, implying that the fully optically thin regime of the jet base is beginning to be accessed at these frequencies [161]. Furthermore, Park et al [162] have found a systematic increase of RM magnitude with increasing frequency in the mm-wave core of several brightest blazars, indicating a greater B-field strength and electron densities towards the jet base.…”
Section: The Innermost Regions Of Blazarsmentioning
confidence: 99%